Twenty-First NSRRC Users' Meeting and Workshops. Issue 2 (3rd March 2016) - Shih, Ming-Tzu; Cheng, Cheng-Maw; Wei, Der-Hsin
Abstract : The Twenty-First NSRRC Users' Meeting was held at the Activity Center of the National Synchrotron Radiation Research Center (NSRRC) in Taiwan from September 9 to 10, 2015. At the same time, celebration of the first light of the Taiwan Photon Source (TPS), achieved at the end of 2014, highlighted the prospective scientific frontiers marked by the TPS storage ring. Jointly organized by the UEC Chair Ying-Hao Chu (National Chiao Tung Univ.) and Cheng-Maw Cheng (NSRRC), the meeting consisted of two plenary sessions and three featured workshops. Nearly 30 distinguished scholars, both domestic and international, were invited to present their research achievements. This highly anticipated event attracted an enthusiastic crowd of more than 370 synchrotron experts, users, and potential users.